How are age and gender related to attitude toward plants and animals? - Strgar, Jelka (Acta biologica slovenica, 2008)
The article examines attitude towards plants and animals in a population of 210 pupils aged 9 to 18. The results support the proposition that animals are generally more interesting to pupils than plants. Their interest was strongly influenced by age, while gender-based difference was only one.
Keywords: Age Factors; Animals; Attitude; Child; dojemanje; Odnos; odnos do rastlin; odnos do živali; Otrok; Plants; Rastline; Sex Factors; spol; Spolni faktorji; starost; Starostni faktorji; učenci; Živali